Effects of transglutaminase pre-crosslinking on salt-induced gelation of soy protein isolate emulsion. (December 2019) - Luo, Kaiyun; Liu, Shutao; Miao, Song; Adhikari, Benu; Wang, Xufeng; Chen, Jie
Abstract: The salt-induced gelation behavior of soy protein isolate (SPI) emulsions was markedly influenced by microbial transglutaminase (TGase) pre-crosslinking. Rheological data showed that when SPI emulsions were incubated with TGase at low concentrations (1 and 3 U/g protein) at 50 °C for 30 min prior to gelation, no change in storage modulus (G′), but enhanced resistance to deformation of the gels was observed. Extensive crosslinking by TGase (5 U/g protein) resulted in severe decreases in gel firmness and fracture properties (yielding stress and strain), likely due to the impairment of hydrophobic bonds and the formation of coarse networks. The water-holding capacity of the gels was significantly enhanced by increased concentrations of TGase. Interactive force analysis indicated that non-covalent interactions and disulfide bonds are the primary forces involved in CaSO4 -induced SPI emulsion gel, but TGase treatment may limit hydrophobic interactions within the gel network. These results are of great potential value for the application of TGase in the food industry. Highlights: Effects of TGase pre-crosslinking on the gelation of CaSO4 -induced SPI emulsion were investigated. Gels pre-incubated with 1–3 U/g TGase improved fracture properties. Extensive crosslinking resulted in coarser gel structure with weak firmness. Incubation with TGase markedly increased the WHC of SPI emulsion gels.